2009
DOI: 10.1093/rheumatology/kep263
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound lung comets in systemic sclerosis: a chest sonography hallmark of pulmonary interstitial fibrosis

Abstract: ULCs are often found in SSc, are more frequent in the diffuse than the limited form and are reasonably well correlated with HRCT-derived assessment of lung fibrosis. They represent a simple, bedside, radiation-free hallmark of pulmonary fibrosis of potential diagnostic and prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
196
1
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(217 citation statements)
references
References 30 publications
4
196
1
16
Order By: Relevance
“…In studies with USG, the B-lines and DLCO were correlated. 7 In our study, both the Warrick score and the number of B-lines were negatively correlated with FVC and DLCO.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In studies with USG, the B-lines and DLCO were correlated. 7 In our study, both the Warrick score and the number of B-lines were negatively correlated with FVC and DLCO.…”
Section: Discussionsupporting
confidence: 52%
“…Gargani et al 7 performed one of the first studies evaluating USG in SSc, comparing HRCT Warrick score and the number of B-lines in USG, and demonstrated that HRCT score and USG were correlated. In another study, detailed USG and simplified USG were performed through 14 intercostal spaces and these were found to be correlated as in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included both patients brought in by ambulance and patients arriving autonomously. Exclusion criteria were: age<18 years, dyspnea following trauma, history of chronic interstitial lung disease (because of confounding pattern at LUS) [17].…”
Section: Setting and Participantsmentioning
confidence: 99%
“…В работе оценивалась информативность УЗИ для выявле-ния ИПЛ при лимитированной и диффузной формах забо-левания. Результаты УЗИ (наличие «легочных комет») со-поставлялись с данными КТВР и функциональных легоч-ных тестов (ФЛТ) [54]. Выраженность легочного фиброза по данным КТВР оценивали с помощью счета Warriсk (по-луколичественная оценка воспалительных и фиброзных изменений легких) [17].…”
Section: рис 1 а-линии в легкихunclassified